Hedonic Test Method for Measuring Instant Pindang Seasoning Powder Preferences - Dea Tio Mareta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Instant seasoning for cooking are commonly known by people who want something practical. Pindang is a typical food of Lampung and South Sumatra Province, consisting of various spices and herbs. Instant pindang seasoning powder made with foam mat drying method using 3 varations of foam additives. The purpose of this study was to determine the level of taste, aroma, and color of instant pindang seasoning powder made with three variations of foam additives, namely 5% (w/w), 10% (w/w), and 15% (w/w). The hedonic test for instant pindang seasoning powder were carried out on 35 panelists. Panelists were faced with 3 samples with 3 different sample numbers. Panelists were asked to assess how much preference for seasoning products using hedonic scale. The hedonic test results showed that, with the addition of 15% (w/w) foam is preferred in terms of color. As for aroma and taste, there were no significant differences between the three products. Keywords: foam mat drying , hedonic test, instant pindang seasoning powder, pindang